2018
DOI: 10.1021/acsami.8b14110
|View full text |Cite
|
Sign up to set email alerts
|

Full-Color Tunable Fluorescent and Chemiluminescent Supramolecular Nanoparticles for Anti-counterfeiting Inks

Abstract: A drive for anti-counterfeiting technology has attracted considerable interests in developing nanomaterials with a wide range of colors and tunable optical properties in solid state. Herein, with a series of conjugated polymers and based on the host−guest driven self-assembly strategy, a color-tunable supramolecular nanoparticle-based system is reported, in which full-color as well as white fluorescence can be achieved. Moreover, this fluorescent platform exhibits reversible photoswitching between quenching an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
89
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(90 citation statements)
references
References 40 publications
1
89
0
Order By: Relevance
“…1820 In recent years, the synthesis of macrocyclic compounds and their functionalization for applications in fluorescent probes have attracted the interest of many researchers. Pillararene was the only highly symmetrical tubular molecule found after the investigation of other macrocyclic molecules, such as crown ethers, cyclodextrin, calixarene, and cucurbituril 21 and has been widely applied in biology, 22 drug delivery, 23 separation process, 24 functional materials, 25,26 and the environment since 2008 owing to its unique rigid structural characteristics and good host–guest recognition performance. 27,28 To date, many researchers have successfully applied pillararenes to ion detection.…”
Section: Introductionmentioning
confidence: 99%
“…1820 In recent years, the synthesis of macrocyclic compounds and their functionalization for applications in fluorescent probes have attracted the interest of many researchers. Pillararene was the only highly symmetrical tubular molecule found after the investigation of other macrocyclic molecules, such as crown ethers, cyclodextrin, calixarene, and cucurbituril 21 and has been widely applied in biology, 22 drug delivery, 23 separation process, 24 functional materials, 25,26 and the environment since 2008 owing to its unique rigid structural characteristics and good host–guest recognition performance. 27,28 To date, many researchers have successfully applied pillararenes to ion detection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, anticounterfeiting technologies have found widespread applications in banknotes, diplomas, certificates, jewelry, medicines, and electronics [1][2][3][4][5][6][7] . Various graphically encoded taggants based on stimuli-responsive molecules have been developed to impede duplication because of their high coding capacity [8][9][10][11][12][13][14][15][16][17][18][19] . However, these are still replicable by counterfeiters due to their low complexity, predictable production process, and deterministic decoding mechanism.…”
mentioning
confidence: 99%
“…Among the various strategies available for anticounterfeiting, fluorescent patterns have been widely used in many fields and play an important role in anticounterfeiting technologies because of the readily detectable chemical characteristics involved [17][18][19][20][21][22] . The information security can be increased dramatically by introducing dynamic fluorescence that can be tuned by external stimuli to the surface pattern.…”
mentioning
confidence: 99%
“…Zhong Yihong et al also demonstrated that the CL imaging array method (Zhong et al, 2019 ). Zuo et al ( 2018 ) have discovered chemiluminescent supramolecular nanoparticles used in anti-counterfeiting inks. Pilar et al ( 2018 ) considered that an aqueous solution of gold nanoparticles can improve the efficiency in electrogenerated chemiluminescent reactions.…”
Section: Introductionmentioning
confidence: 99%